Absolute geolocation accuracy of high-resolution spotlight TerraSAR-X imagery – validation in Wuhan. Issue 4 (1st October 2016) - Wang, Jinghui; Balz, Timo; Liao, Mingsheng
Abstract: TerraSAR-X (TSX) can acquire high-resolution SAR images and due to its high orbit precision as well as its ability to acquire data from different off-nadir viewing angles, the high-precision stereo geolocation can be obtained. In this study, we investigate the absolute geolocation accuracy of TSX high-resolution images in Wuhan, China. We present a direct stereo SAR geolocation method and analyze the 2D and 3D geoposition accuracy of two corner reflectors. The sub-meter localization accuracy was achieved using only atmospheric correction information available in the TSX metadata.